State, labor, and the transition to a market economy : Egypt, Poland, Mexico, and the Czech Republic - Paczyńska, Agnieszka, 1967- (Pennsylvania State University Press, 2009)
"Explores what facilitates or hinders social group attempts to influence the process of economic restructuring and reconstruction of state-society relations by focusing on organized labor's response to privatization of the public sector during the first decade of reforms. Compares Poland, Egypt, Mexico and the Czech Republic"--Provided by publisher